Pindar's Prosodia: introduction, text, and commentary to selected fragments - Prodi, E (2013)
This dissertation examines the surviving remains of the two books of Pindar’s Prosodia. The introduction falls into four parts. The first is concerned with gathering the evidence for the books, through a review of their ancient testimonia (Chapter 1) and of the indirect and direct transmission of their fragments (Chapter 2); the second is concerned with the prosodion as a poetic genre, with some introductory remarks (Chapter 3) followed by an investigation of the collected evidence for the notion of prosodion in describing poetic texts (Chapter 4) and in later scholarship and generic theory (Chapter 5); the third combines the results of the first two into an analysis of the surviving fragments of Pindar’s Prosodia and an inquiry on the generic principles that shaped the collection (Chapter 6); the fourth consists of a descriptive catalogue of the papyrus manuscripts that contribute to the text of Pindar’s Prosodia (Chapter 7). The critical text of the eighteen main fragments and groups of fragments is followed by an introduction and line-by-line commentary to six of them, nos. 1, 2, 3, 5, *6, and *7 (= fr. 89 Snell-Maehler and ‘Paeans’ 14, 15, 6.123-183, 17, and 18).